2003
DOI: 10.1016/s0079-6107(03)00003-8
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-activated chloride channels in cardiac physiology and pathophysiology

Abstract: Characteristics and functions of the cardiac swelling-activated Cl current (I(Cl,swell)) are considered in physiologic and pathophysiologic settings. I(Cl,swell) is broadly distributed throughout the heart and is stimulated not only by osmotic and hydrostatic increases in cell volume, but also by agents that alter membrane tension and direct mechanical stretch. The current is outwardly rectifying, reverses between the plateau and resting potentials (E(m)), and is time-independent over the physiologic voltage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 79 publications
5
124
1
1
Order By: Relevance
“…Thus, membrane Cl − channels have the unique ability, compared with cation channels, to contribute both inward as well as outward current during cardiac action potential (9,13,14). Consequently, activation of VRAC current should decrease the action potential duration (APD) and thereby the effective refractory period (ERP), and should depolarize membrane potential (15); it may also contribute to the development of stretchinduced membrane depolarizations and arrhythmias (9,14).…”
Section: (5) the CLmentioning
confidence: 99%
“…Thus, membrane Cl − channels have the unique ability, compared with cation channels, to contribute both inward as well as outward current during cardiac action potential (9,13,14). Consequently, activation of VRAC current should decrease the action potential duration (APD) and thereby the effective refractory period (ERP), and should depolarize membrane potential (15); it may also contribute to the development of stretchinduced membrane depolarizations and arrhythmias (9,14).…”
Section: (5) the CLmentioning
confidence: 99%
“…Patch-clamp studies have now identified at least eight types of Cl -currents in cardiac cells from different regions of the heart and in different species. The biophysical, pharmacological and molecular properties of these Clchannels have been well characterized and are summarized in Table 1 Hume et al, 2000;Baumgarten & Clemo, 2003;Duan et al, 2005;Duan, 2009). Several of these Cl -channels have been found to be expressed in SAN of different species (Table 1).…”
Section: -Channels In the Heartmentioning
confidence: 99%
“…Although it has been suggested that stretch and swelling activate the same anion channel in some non-cardiac cells, further study is needed to determine whether this is true in cardiac myocytes. Baumgarten's laboratory has recently demonstrated that I Cl,swell in ventricular myocytes can be directly activated by mechanical stretch through selectively stretching β1-integrins with mAb-coated magnetic beads (Browe & Baumgarten, 2003;Baumgarten & Clemo, 2003;Browe & Baumgarten, 2004;Browe & Baumgarten, 2006). The stretch-activated Cl -current may contribute to the pacemaker rhythm under physiological conditions, since the stimulus is almost continuously present in the intact heart (Hagiwara et al, 1992).…”
Section: Clvol and Clc-3 CLmentioning
confidence: 99%
See 2 more Smart Citations